1973
DOI: 10.1159/000122116
|View full text |Cite
|
Sign up to set email alerts
|

Pars Intermedia of the Hypophysis of Rats after Early-Postnatal Lesions of the Basal Hypothalamus: Quantitative and Qualitative Observations

Abstract: Lesions were made by electrical coagulation in the base of the hypothalamus of rats, 20 to 24 h after birth. Subsequent growth of the hypophysis was examined volumetrically and histologically on the 40th and 60th days after the operation, paying special attention to the pars intermedia. Growth retardation of the hypophysis was noticeable after 60 days in rats with lesions of the hypophysial stalk (groups 1 and 2) and the posterior portion of the median eminence (group 4), especially in animals in which the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These vesicles are observed 32 and 56 h after EB injection and 24 and 48 h after administration, following MSH release. Similar vesicles have also been observed in rat PI cell culture (Back et al 1982) and in PI of rats with hypothalamic lesions (Ooki et al 1973), conditions where the -MSH release was stimulated. In con¬ trast, the 'empty vesicles' are rarely seen in normal PI and in chronically ovariectomized rats in which the -MSH release is inhibited.…”
Section: Discussionsupporting
confidence: 77%
“…These vesicles are observed 32 and 56 h after EB injection and 24 and 48 h after administration, following MSH release. Similar vesicles have also been observed in rat PI cell culture (Back et al 1982) and in PI of rats with hypothalamic lesions (Ooki et al 1973), conditions where the -MSH release was stimulated. In con¬ trast, the 'empty vesicles' are rarely seen in normal PI and in chronically ovariectomized rats in which the -MSH release is inhibited.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to H amori [1960], we did not observe cytological changes in the pars intermedia of lesioned rats. In addition, electronmicroscopical studies [Ooki et al, 1973] showed a normal appearance of pars intermedia cells 40-60 days after lesioning the mediobasal hypothalamus of infant rats. Thus, although elevated melanotropic activity has been reported in rat blood after destruction of the hypothalamo-hypophysial connection [Carrillo et al, 1973;Celis et al, 1973], there is no convincing morphological evidence for an endocrine hyperactivity of the pars intermedia.…”
Section: Discussionmentioning
confidence: 94%
“…With the elec¬ tron microscope, both neurosecretory-type fibres and fibres apparently devoid of the characteristic neurosecretory granules have been described coursing within the pars intermedia of the cat, rat, ferret, guinea-pig and rabbit (Bargmann & Knoop, 1960;Kurosumi et al 1961 ;Ziegler, 1963;Kobayashi, 1964Kobayashi, , 1965Howe & Maxwell, 1966, 1968Bargmann, Lindner & Andres, 1967;Wittkowski, 1967;Vincent & Kumar, 1968Vincent, 1969 ;Cameron & Foster, 1971). Nerve terminals, with and with¬ out neurosecretory granules, make contact with Type 1 pars intermedia cells (Kuro¬ sumi et al 1961;Ziegler, 1963;Green, 1964;Howe & Maxwell, 1966, 1968Vincent & Kumar, 1968Vincent, 1969;Ooki, Kotsu, Kinutani & Daikoku, 1973).…”
Section: Nervous Control (A) Innervation (I) Histologymentioning
confidence: 99%
“…The nerve fibres enter the pars intermedia by way of the pituitary stalk and neural lobe (Hillarp & Jacobsohn, 1943;Fuxe, 1964;Vincent, 1969); they disappear after stalk section (Vincent, 1969;Ooki et al 1973). Although their origins have not yet been defined precisely, it is clear that most are axons arising from perikarya situated in the hypothalamus (see Hillarp & Jacobsohn, 1943;Green & Harris, 1947;Holmes, 1961;Fuxe, 1964, for references), in particular the para ventricular and supraoptic nuclei (Olivecrona, 1957; Olmos, Orias & Tomatis, 1967;Howe & Thody, 19696, c) and the periventricular nucleus (Nobin, Björklund & Stenevi, 1972).…”
Section: Nervous Control (A) Innervation (I) Histologymentioning
confidence: 99%